Makna Bimbingan Belajar bagi Orangtua Siswa di Indralaya Kabupaten Ogan Ilir - Akhmad Syafe`i; Zulfikri Suleman; Dadang Hikmah Purnama (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
This study aims to explain the meaning of tutoring center for parents in Indralaya, Ogan Ilir Regency, using qualitative descriptive research, based on transcendental phenomenology theory by Edmund Husserl who reviewed and revealed the meaning of consciousness, purpose, and intersubjectivity of the parents’s experience who involving their children in the tutoring center in Indralaya, Ogan Ilir Regency, and the linkage between the meaning of consciousness, pupose and intersubjectivity of the experience itself, where the data obtained through interviewing 18 (eightteen) parents who involving their children in tutoring center, 4 (four) tutoring staff and 3 (three) students who joining tutoring center in Indralaya, Ogan Ilir Regency. This research result shows that awareness of parents to involve their children in the tutoring center because parents see the will of their children and realize the competition which is increasing from time to time, as for the purpose of the parents because their children need more to mastery the material and strong desire to pass the next level of education, then the meaning of (intersubjectivity) experience of involving children in the tutoring center as a supporter of formal education as well as education costs. The relation between consciousness, purpose and intersubjectivity (experience) lies in a sequential process that starts from the parents’s awareness, after that there are purpose that appears, then the intersubjectivity process in the form of parents’s experience, so that the meaning of tutoring center for parents is as supporter of formal education and as a high-cost education/ expensive.